Rekayasa Tempat Parkir Kendaraan Mobil Berbasis Teknologi Informasi - Husain Husain; Asmah Akhriana; Herlinda Herlinda; Ahmad Ahmad; Nurdiansah Nurdiansah; Risma Putri Willy Tutang (PROtek : Jurnal Ilmiah Teknik Elektro, 2022)
The availability of parking lots is a must for perkatoran, shopping centers (malls), universities and others.Â  Along with the ability of the public to have vehicles, both two-wheeled and four-wheeled vehicles, it makes parking spaces difficult and takes a long time to get a parking space, this is because there is no service regarding information on the availability of empty parking slots, so there is no marker to know whether the parking lot is fully filled or not.Â  It is necessary to design a parking monitoring system tool, which aims to provide information on the availability of parking slots. Using the application design method by utilizing several object detection sensors including the Infrared Proximity Sensor and using the Message Queuing Telemetry Transport (MQTT) protocol which functions as a wireless communication protocol. The results of this study show that the system works as expected, that the sensor can detect parking objects that are filled or still empty and the system data communication also works well, namely the sensor sends data to wemos D1, then sent to the MQTT Broker (server) then resumes to wemos D1 and then the data is sent to the message viewer device, namely monitors and LEDs. The LED light as an indicator gives a message, if the LED lights up in green, it means that the parking lot is not filled and if the LED lights up red, it means that the parking slot is filled.